2019
DOI: 10.1016/j.neuron.2019.01.050
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanosensitive Ion Channel Piezo Inhibits Axon Regeneration

Abstract: Highlights d Piezo cell autonomously inhibits axon regeneration in Drosophila sensory neurons d Piezo channels are activated after axon injury or during axon regeneration d Piezo inhibits axon regeneration through calcium signaling, Nos, and PKG d Piezo1 also inhibits axon regeneration in mammals in vitro and in vivo

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
134
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 147 publications
(159 citation statements)
references
References 86 publications
(121 reference statements)
6
134
0
Order By: Relevance
“…Treating human umbilical vein endothelial cells (HUVECs) or prostate cancer cell lines (PC‐3 and LNCaP) with GsMTx4 causes a decrease in cell migration (Li et al, ; Maroto, Kurosky, & Hamill, ) but enhances neurite outgrowth in Xenopus spinal cord explants (Jacques‐Fricke, Seow, Gottlieb, Sachs, & Gomez, ). More recently, Song et al () have shown that Piezo1 activation can inhibit neural regeneration in Drosophila. Here, we show that astrocytes exposed to LPS (to induce Piezo1 expression) and GsMTx4 (to simultaneously block Piezo1 channel opening) migrate faster than astrocytes stimulated with LPS and Yoda1 (which activates Piezo1 channels).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Treating human umbilical vein endothelial cells (HUVECs) or prostate cancer cell lines (PC‐3 and LNCaP) with GsMTx4 causes a decrease in cell migration (Li et al, ; Maroto, Kurosky, & Hamill, ) but enhances neurite outgrowth in Xenopus spinal cord explants (Jacques‐Fricke, Seow, Gottlieb, Sachs, & Gomez, ). More recently, Song et al () have shown that Piezo1 activation can inhibit neural regeneration in Drosophila. Here, we show that astrocytes exposed to LPS (to induce Piezo1 expression) and GsMTx4 (to simultaneously block Piezo1 channel opening) migrate faster than astrocytes stimulated with LPS and Yoda1 (which activates Piezo1 channels).…”
Section: Discussionmentioning
confidence: 99%
“…Piezo1 is a nonselective cation channel expressed on the outer cell membrane and is permeable to extracellular calcium (Ca 2+ ) influx (Gottlieb & Sachs, 2012;Li et al, 2015). The calcium-mediated mechanotransduction signaling cascades activated by Piezo1 channel opening are important in a range of developmental and physiological processes including neuronal differentiation (Pathak et al, 2014), axon guidance (Koser et al, 2016), confinement-sensing and cell migration (Hung et al, 2016), neuronal regeneration (Song et al, 2019), shear stress-mediated vasodilation , and immune cell activation (Liu et al, 2018). However, the intracellular molecular mechanisms that underlie Piezo1's role in many of the above cellular processes have yet to be fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Piezo1, the only known homolog of Piezo2, mediates the detection of mechanical force in various cell types inside the body, including interoceptive mechanoreceptors from the nodose ganglion and neurons in the central nervous system (CNS), where it does not encounter significant fluctuations in temperature (18)(19)(20). Piezo1 activation is thought to be triggered primarily by membrane tension (21)(22)(23)(24)(25)(26).…”
mentioning
confidence: 99%
“…The exact roles of Ca 2+ signals in controlling regeneration ranges from promoting to inhibiting regeneration (Chierzi et al, 2005;Enes et al, 2010;Song et al, 2019;Tedeschi et al, 2016). Our results suggest that Ca 2+ spikes promote C3da and C4da neuron regeneration.…”
Section: Ca 2+ Signaling and Axon Regenerationmentioning
confidence: 73%